0209 Ckdu: intervention to policy * this is part of the mini-symposium organised by tord kjellstrom. (21st August 2017) - Glaser, Jason; Jakobsson, Kristina; Wesseling, Ineke; Wegman, David; Lucas, Becky; Bodin, Theo; Ekstrom, Ulf; Weiss, Ilana
Abstract : Background: In Mesoamerica CKDu(Chronic Kidney Disease of unknown cause) is epidemic among sugarcane workers and present in other workers. Excessive heat stress and workload are believed to contribute to onset and acceleration of CKDu. The Worker Health and Efficiency (WE) Program is the first evaluated intervention to address excessive heat stress and workload in sugarcane workers. We used the resulting press, political and industry attention to push for a wider agenda of worker protections. Objectives: Evaluate impact of intervention on patterns of heat illness/dehydration, kidney function, physical workload and productivity. Demonstrate need for governments and industry to address CKDu and excessive heat stress in sugarcane- and other workers. Methods: The WE intervention was piloted in two cohorts of workers, one inland and one coastal sugarcane cutters (totaling 117 individuals); thus, allowing assessment of the intervention via self-controls. Concurrently, outreach to industries and governments was conducted to exchange information. Using press and myriad contacts, private and public policy began to rapidly change. Results: Pilot data analysis demonstrated a decrease in heat-related illness, improved hydration, and possibly a stabilisation in kidney function. Marked increase in productivity was also observed. The results drove policy discussions and measurable change in several companies, and the U.S. and Costa Rican Governments. Conclusion: An evidenced-based dialogue between sugar industry farmers, millers, buyers, and governments was created. There are several challenges that remain, and navigating the path to where we are holds valuable lessons for those doing similar work.